Analisis Kegiatan Fullday School dalam Membentuk Karakter Religius pada Siswa Kelas IV SDIT Ar-Ridho - Yunita Damayanti; Muhammad Imam Muttaqjin; Ahmad Arif Fadilah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This study aims to describe the effect of Fullday School activities in the formation of religious character in fourth grade students of SDIT AR-RIDHO Binong, Tangerang Regency. This type of research is a qualitative descriptive research conducted by analyzing and explaining the activities of the Fullday School subject to the research, namely the fourth grade students of SDIT AR-RIDHO. Data collection techniques used in this study include observation, interviews, and documentation which are then collected using descriptive methods that describe the data to obtain a real form from the respondents, making it easier for researchers or other people who are interested in the results of the research conducted. The results of the study show that the Fullday School system can be a very supportive system in the process of forming religious character in fourth grade students of SDIT AR-RIDHO BINONG, Tangerang Regency. Based on the research, that the analysis of Class IV Fullday School activities at SDIT AR-RIDHO BINONG has been carried out well with the support of adequate facilities, infrastructure, superior human resources, interactive intra-curricular, co-curricular and extra-curricular learning.